Assessing the Inequality of Early Child Development in China - A Population-Based Study - Yunting Zhang, PhD; Le Kang, PhD; Jin Zhao, PhD; Prof. Yingquan Song, PhD; Prof. Fan Jiang, MD, PhD; Chunling Lu, PhD (Elsevier, 2021)
Background: As a country with the second largest child population in the world, China has little population-level evidence on who has been left behind in early childhood development (ECD). Knowledge of inequalities in ECD will inform the Chinese government in policies on promoting ECD and guide global-level monitoring on ECD progress. Methods: Using data from the first wave of ECD surveys conducted in China at the least-developed region, most-developed region, and a megacity (Shanghai) in 2017 and 2018, we measured population-level ECD with early Human Capability Index for a total of 63,559 children aged 36-59 months old. A child was classified as developmentally on track if his/her overall development score was above the 20th percentile of the pooled populations. We measured inequalities in ECD with the absolute inequality in five domains: gender/sex, family income, maternal schooling, residential Hukou, and migrant- or left-behind status. Besides observed inequalities, we used a multilevel logistic regression model to generate adjusted inequalities. Findings: Children developmentally on track ranges from 71% (95% CI 70 to 72%) in the least-developed region, 82% (95% CI 81 to 83%) in the most-developed region, and 86% (95% CI 85 to 87%) in Shanghai. Significant unadjusted inequalities in ECD were observed in all five dimensions. After controlling for other socioeconomic factors, significant differences remained in three dimensions: those living in the poorest families, or with lower maternal schooling, or boys were less likely to be developmentally on track than their counterparts (lower by 10[95% CI 8 to 11]-15[95% CI 13 to 17], 7[95% CI 5 to 10]-10[95% CI 7 to 12], and 5[95% CI 4 to 6]-6[95% CI 5 to 8] percentage points respectively). Interpretation: Efforts of reducing ECD inequalities in China shall focus primarily on reducing poverty and improving maternal education. Funding: National Natural Science Foundation of China (81773443), Shanghai Committee of Science and Technology (2018SHZDZX05), Shanghai Municipal Health Commission (GWV-10.1-XK07; GDEK201708), Shanghai Education Committee, Chinese Social Science Foundation (BFA140046), Macao Tong Chai Charity Association, Beijing Sany Charitable Foundation, China Medical Board (#20-388), UNICEF, Faculty Grant of Brigham & Women's Hospital, Economic and Social Research Council [grant reference number ES/T003936/1'] as a UKRI Collective Fund Award "UKRI GCRF Harnessing the Power of Global Data to Support Young Children's Learning and Development Collaborative.''